A model to calculate effects of atmospheric deposition on soil acidification, eutrophication and carbon sequestration. (May 2016) - Bonten, Luc T.C.; Reinds, Gert Jan; Posch, Maximilian
Abstract: Triggered by the steep decline in sulphur deposition in Europe and North America over the last decades, research and emission reduction policies have shifted from acidification to the effects of nitrogen (N) deposition and climate change on plant species diversity and carbon (C) sequestration in soils and biomass. Consequently, soil-ecosystem models need to include detailed descriptions of C and N processes, and ideally provide output that link to plant species diversity models. We describe an extension of the Very Simple Dynamic (VSD) model, called VSD+, which includes an explicit description of C and N turnover. Model simulations for three forest stands, which differ in N deposition and soil C/N ratios, show that VSD+ can well predict both trends and absolute values of NO3 and NH4 concentrations in soil and stream waters, soil C/N ratios and pH, which makes VSD+ suitable for providing input for plant species diversity models. Highlights: Air pollution policies have shifted from acidification to eutrophication and climate change. VSD+ is a soil-chemical model that includes explicit C and N dynamics. The model adequately predicts NO3 concentrations, pH and C and N dynamics. Output of the model is suitable input for plant species diversity models.